Seed Priming with Glass Waste Microparticles and Red Light Irradiation Mitigates Thermal and Water Stresses in Seedlings of Moringa oleifera - Patrícia da Silva Costa; Rener Luciano de Souza Ferraz; José Dantas Neto; Semako Ibrahim Bonou; Igor Eneas Cavalcante; Rayanne Silva de Alencar; Yuri Lima Melo; Ivomberg Dourado Magalhães; Ashwell Rungano Ndhlala; Ricardo Schneider; Carlos Alberto Vieira de Azevedo; Alberto Soares de Melo (Plants, 2022)
The association between population increase and the exploitation of natural resources and climate change influences the demand for food, especially in semi-arid regions, highlighting the need for technologies that could provide cultivated species with better adaptation to agroecosystems. Additionally, developing cultivation technologies that employ waste materials is highly desirable for sustainable development. From this perspective, this study aimed to evaluate whether seed priming with glass waste microparticles used as a silicon source under red light irradiation mitigates the effects of thermal and water stress on seedlings of Moringa oleifera. The experimental design was set up in randomized blocks using a 2 × 2 × 2 factorial arrangement consisting of seed priming (NSP—no seed priming, and SPSi—seed priming with glass microparticles under red light irradiation), soil water replenishment (W50—50%, and W100—100% of crop evapotranspiration—ETc), and temperature change (TC30°—30 °C day/25 °C night and TC40°—40 °C day/35 °C night). Seed priming with glass microparticles under red light irradiation mitigated the effects of thermal and water stress on seedlings of Moringa oleifera seedlings through the homeostasis of gas exchange, leaf water status, osmotic adjustment, and the antioxidant mechanism.